Keputusan Pengguna Gopay dari Aspek E-Service Quality, Promosi dan Harga - Fitriani Latief Latief; Ahmad Firman; Dirwan Dirwan (UNIVED Press, 2023)
The purpose of this study was to examine the effect of e-service quality, promotion and price on the decision to use Gopay. This study uses a causal analysis design with quantitative research methods. The population in this study is ITB Nobel Indonesia students using the Gopay application whose number is not known with certainty, while the sampling method uses non-probability sampling with purposive sampling technique with respondent criteria 1) respondents know about Gopay; 2) respondents have used the Gopay application more than 2 times. The number of samples used in this study were 100 respondents. The data in this study were directly obtained from filling out a questionnaire (questionnaire) given to respondents in the form of closure which would then be answered by the respondent. The data analysis technique used in this research is descriptive analysis, classical assumption test and multiple linear regression analysis. The results of this study found that e-service quality and promotion had a positive and significant effect on the decision to use Gopay. While the price has no positive and insignificant effect on the decision to use Gopay.